Organic amendments increase the flow uniformity of energy across nematode food webs. (July 2022) - Wan, Bingbing; Hu, Zhengkun; Liu, Ting; Yang, Qian; Li, Daming; Zhang, Chongzhe; Chen, Xiaoyun; Hu, Feng; Kardol, Paul; Griffiths, Bryan S.; Liu, Manqiang
Abstract: Energy dynamics within ecological communities are important in delivering ecosystem services. However, it remains elusive how the energy fluxes within soil food webs respond to agricultural fertilization regimes. Here, we studied the effects of long-term organic amendments and mineral fertilizers on the energetic structure of soil nematodes from a food-web perspective. We replicated our experiment in a rice paddy and in an upland maize cropping system. Results showed that the abundance of most trophic groups was higher in organically amended soils compared with mineral fertilizer treatments in both systems. Organic amendments, but not mineral fertilizers, increased the energy flux of total nematodes and most trophic groups compared with the no-fertilizer treatment. Furthermore, organic amendments increased the relative allocation of energy flux to microbivores but decreased the relative allocation to herbivores, supporting a higher flow uniformity than mineral fertilizers. We further found that organic amendments favored a higher total energy flux by supporting a greater nematode diversity, while sustained a higher flow uniformity by altering nematode community composition. Taken together, the result provides the evidence that a complex and species-rich community could transfer more energy to support ecosystem services. A broader perspective on linkages of biodiversity and energy dynamics spanning multitrophic groups is crucial for sustainable management, particularly in the light of non-random species loss under future environmental change. Graphical abstract: Image 1 Highlights: Organic amendments increased total energy flux and flow uniformity. High flow uniformity resulted from increasing relative energy flux of microbivores. Energy fluxes and flow uniformity were positively linked with nematode diversity. Effect of diversity decline on energy loss was stronger in paddy than upland fields.